(untitled) (Journal of the College of Basic Education, 2022)
The research aims to identify:Identifying the effect of using exercises with variable weights in developing the special strength to perform the skill of football scoring accuracy for the youth group.The experimental method was used, and the research sample was selected from the players of Al-Sinaa Sports Club for the youth category, aged (16-18) years.The results resulted in the emergence of significant differences in all special strength tests, and the technical performance of the experimental group in the pre and post test, in favor of the post test, as well as the prepared curriculum that has a positive impact on the experimental research sample.